Multimodal Prominence Marking in Semi-Spontaneous YouTube Monologs: The Interaction of Intonation and Eyebrow Movements - Berger, Stephanie; Zellers, Margaret (Frontiers in Communication, 2022)
Both facial expressions like eyebrow movements and prosodic characteristics like pitch height and the position of the pitch accent relative to the prominent syllable play an important role in prominence marking, which in turn is used by YouTubers and other public speakers alike to engage their audience. We analyze the co-occurrence of eyebrow movements and pitch accents of differing prominence levels produced by a sample of English-speaking YouTubers, and the height and position of those pitch accents. We annotated pitch accents, and analyzed videos using OpenFace 2.0, using three different eyebrow movement measures: eyebrow landmarks, distance between eyebrow and eye landmarks, and Action Units (facial expressions). We found that pitch height and eyebrow movements are positively correlated for at least some of the measures for all speakers. We also found that it is more likely for a medial or late pitch accent to arise at the time of an Action Unit connected to the eyebrows than an early accent, while there was no effect of the prominence level. However, we did not find evidence for a close temporal coordination of pitch movement and eyebrow movement. Finally, we found speaker-individual differences in the use of eyebrow movements and pitch accents, but also some slight indications of an effect for geographical origin of the speaker.